Durability of hybrid fiber reinforced concrete at various environmental media - Eslam Ibrahim Nasr Elhawary; Ashraf Hassan Elsafoury; Seleem Saleh Elsayed Ahmad (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2022)
Fiber’s addition to concrete mixture attracts researchers to determine the effect of fiber type on durability properties of hybrid performance concrete. In the present work, steel and polypropylene fibers are used in hybrid form in the experimental program. The objective of this paper is to investigate the mechanical properties of hybrid fiber reinforced concrete subjected to four various media: air, water, sodium chloride, and magnesium sulphate with a 7% concentration. The results showed that using hybrid fibers which consist of 1% steel fiber and 0.3% polypropylene fiber improved the compressive strength, splitting tensile strength, and flexural strength for different media for up to 360 days.